DETERMINASI PROFITABILITAS PERUSAHAAN RETAIL: PERAN MANAJEMEN MODAL KERJA, LIKUIDITAS, DAN LEVERAGE - Muhammad Rivandi; Dodi Pernandes; Lidya Martha; Teguh Hidayat (Jurnal Manajemen Dan Akuntansi Medan, 2026)
Profitability is a key indicator of financial performance that reflects a company’s ability to generate profits through the efficient utilization of its assets. This study aims to analyze the effect of working capital management, liquidity, and Leverage on the profitability of retail companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This research employs a quantitative approach with a causal associative method. The research sample consists of 16 retail companies, selected using a purposive sampling technique. The data used in this study are secondary data obtained from the companies’ annual financial statements. Data analysis was conducted using panel data regression after fulfilling the required classical assumption tests and selecting the appropriate regression model. The results indicate that working capital management has a positive effect on profitability, while liquidity has a negative effect on profitability. Meanwhile, Leverage does not have a significant effect on the profitability of retail companies. Simultaneously, working capital management, liquidity, and Leverage significantly affect profitability. The implications of this study suggest that retail companies should improve the efficiency of working capital management and maintain optimal liquidity levels to enhance financial performance, while managing debt usage prudently to avoid excessive financial risk.